A New Species of Protosmia Ducke From Spain With Notes on Related Species (Hymenoptera: Megachilidae) - Terry Griswold; Frank D. Parker (Psyche: A Journal of Entomology)
A trap-nesting program in northern Spain undertaken in cooperation with Dr. Enrique Asensio (Instituto Nacional de Investigaciones Agrarias, Valladolid) over the past few years has resulted in numerous nests of megachilids. One of these represents a new species of Protosmia Ducke. It is described here in order to make the name available for the description of its nesting biology, and is named in honor of Dr. Asensio, in recognition of his considerable help in this trap-nesting study.